Graphitic carbon nitride (g-C3N4) based heterogeneous single atom catalysts: synthesis, characterisation and catalytic applications. Issue 16 (5th April 2023) - P, Suja; John, Jubi; Rajan, T. P. D.; Anilkumar, Gopinathan M; Yamaguchi, Takeo; Pillai, Suresh C.; Hareesh, U. S.
Abstract : The ease of anchoring single atoms on the g-C3 N4 matrix, through its abundant nitrogen sites, facilitates a variety of single atom catalysts for applications in multiple domains of catalysis. Abstract : Graphitic carbon nitride (g-C3 N4 ), the well-known visible light active, two-dimensional organic semiconductor is gaining further prominence as a potential matrix for developing heterogeneous single atom catalysts. g-C3 N4 by virtue of its abundant and periodically separated nitrogen atoms effectively stabilises single atoms of metal through the electron lone pairs of nitrogen acting as anchoring sites. Herein, the synthetic strategies adopted for the development of g-C3 N4 based single atom catalysts (SACs) are summarised in detail for an understanding of the state-of-the-art designing of g-C3 N4 SACs. Advanced characterisation techniques like extended X-ray absorption fine structure (EXAFS), X-ray absorption near-edge structure (XANES), electron energy-loss spectroscopy (EELS), X-ray photoelectron spectroscopy, and aberration-corrected high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) offer valuable inputs to determine the electronic and geometric structure of g-C3 N4 based SACs are discussed. Furthermore, the experimental and computational efforts carried out in demonstrating the potential applications of g-C3 N4 SACs in the field of photocatalysis, organic reaction catalysis and electrocatalysis are reviewed. The challenges associated with the practical utility of g-C3 N4 based SACs and their future perspectives in heterogeneous catalysis are outlined.